AISF-SIMTI Position Paper: The appropriate use of albumin in patients with liver cirrhosis. Issue 1 (January 2016) - ,; ,; Caraceni, Paolo; Angeli, Paolo; Prati, Daniele; Bernardi, Mauro; Alessandria, Carlo; Riggio, Oliviero; Salerno, Francesco; Maria Liumbruno, Giancarlo; Bennardello, Francesco; Piccoli, Pierluigi; et al.
Abstract: The use of human albumin is common in hepatology since international scientific societies support its administration to treat or prevent severe complications of cirrhosis, such as the prevention of post-paracentesis circulatory dysfunction after large-volume paracentesis and renal failure induced by spontaneous bacterial peritonitis, and the treatment of hepatorenal syndrome in association with vasoconstrictors. However, these indications are often disregarded, mainly because the high cost of human albumin leads health authorities and hospital administrations to restrict its use. On the other hand, physicians often prescribe human albumin in patients with advanced cirrhosis for indications that are not supported by solid scientific evidence and/or are still under investigation in clinical trials. In order to implement appropriate prescription of human albumin and to avoid its futile use, the Italian Association for the Study of the Liver (AISF) and the Italian Society of Transfusion Medicine and Immunohaematology (SIMTI) nominated a panel of experts, who reviewed the available clinical literature and produced practical clinical recommendations for the use of human albumin in patients with cirrhosis.